A Triterpenoid from Moringa pterygosperma - Mishra, A.; Dubey, G.P. (Asian Journal of Chemistry, 2010)
A triterpene is isolated direct from the hexane extract of the bark of Moringa pterygosperma. This is identified as leupol.